A comparative study in treatment of childhood vitiligo 0.03% tacrolimus versus 0.03% tacrolimus and topical steroids - Anandan Venkatesan; Rashmi Sriram; Sindhuja Balaji; T K Anandhi (Wolters Kluwer Medknow Publications, 2021)
Background: Vitiligo is an idiopathic, acquired cutaneous achromia, characterized by circumscribed milky white macules. It develops before the age of 20 years in 50% of the patients and before the age of 10 years in 25% of the patients. Methods: This was a 2-year, prospective, comparative study conducted in vitiligo patients with 1 year of active intervention. Fifty patients in the age group of 2-14 years were enrolled in the study. Randomization was performed according to computer-generated random code. Patients with code A received treatment with 0.03% tacrolimus alone and patients with code B received treatment with 0.03% tacrolimus and topical steroids. The primary efficacy variable was the Vitiligo Area Severity Index (VASI), and the secondary efficacy parameter includes the Physician's Global Improvement Score which was computed at the end of the study. The statistical analysis was carried out using statistical software STATA 6.0. Results: Out of these 50 patients, 47 patients completed the study for a period of 1 year. The area-wise VASI reduction and VASI reduction in vitiligo types were analyzed in patients with code A and code B. The mean Physician's Global Assessment Score was 3.041 in the tacrolimus group, and it was 3.261 in the tacrolimus with steroid group. Conclusion: This shows that 0.03% tacrolimus can be effectively used as topical monotherapy in patients with localized stable vitiligo without the adverse effects of topical steroids.